Differential regulation of SOX9 protein during chondrogenesis of induced pluripotent stem cells versus mesenchymal stromal cells: a shortcoming for cartilage formation - Diederichs, Solvig; Gabler, Jessica; Autenrieth, Jennifer; Kynast, Katharina; Merle, Christian; Utikal, Jochen; Richter, Wiltrud (Stem Cells and Development, 2016)
Induced pluripotent stem cells (iPSCs) are an attractive cell source for cartilage regeneration, but current in vitro chondrogenic differentiation protocols yield insufficient results. In search for shortcomings of iPSC chondrogenesis, this study investigated whether SOX9 protein was adequately regulated during multiphase chondrogenic differentiation of two human iPSC lines in a comparable manner like during mesenchymal stromal cell (MSC) chondrogenesis. Upon generation of intermediate mesenchymal progenitor cells (iMPCs), SOX9 was induced and reached variable protein levels compared to MSCs. Along with an altered condensation behavior, iMPC cartilage formation was less robust compared to MSCs and better in the iMPC line with higher SOX9 protein levels. Despite efficient Smad-2/3 phosphorylation, TGF-β-driven chondrogenic stimulation downregulated SOX9 protein in iMPCs rather than increasing levels like in MSCs. Chondrogenesis was further improved by cotreatment with TGF-β + BMP-4, which appeared to shorten the duration of the SOX9 protein decline. However, this was insufficient to overcome heterogenic outcome and came at the expense of undesired hypertrophy. In iMPCs, but not MSCs, high levels of the SOX9-antagonizing hsa-miR-145 correlated with low SOX9 protein quantity. Thus, considerable iMPC heterogeneity with variable SOX9 protein levels, an altered condensation pattern, and low early SOX9 inducibility appeared as critical shortcomings of iPSC chondrogenesis. We suggest consistent quality of intermediate cell populations with high SOX9 protein induction as important indicators to obtain robust cartilage formation from iPSCs. The impact of this study is the identification of a SOX9 protein regulation opposite to MSC chondrogenesis that will now enable a selective adaptation of the currently limited protocols to the specific needs of iPSCs.